FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KELUARGA DALAM MERAWAT PENDERITA HIPERTENSI - Nadila Cesar Wuri; Ardiansyah; Tasya Anggraini (Institut Citra Internasional, 2025)
Family stress is a psychological and emotional response that arises due to pressure during caring for family members with chronic diseases including hypertension. This study aims to determine the factors associated with family stress in caring for patients with hypertension. This study used a cross-sectional design and data analysis techniques using the Chi-square test, with a sample of 106 respondents taken by purposive sampling from all families caring for patients with hypertension in the Girimaya Community Health Center Working Area in 2025. The results showed that factors significantly associated with family stress were financial burden (ρ = 0.000), level of knowledge (ρ = 0.000), employment status (ρ = 0.010), duration of illness (ρ = 0.000), and complications (ρ = 0.007). The conclusion of this study is that financial burden, level of knowledge, employment status, duration of illness, and complications in Hypertension patients have a relationship with the level of family stress in caring for Hypertension patients in the Girimaya Community Health Center Working Area in 2025. It is hoped that patient families can increase their knowledge about Hypertension management through health education, while the community health center can expand health promotion programs for families/caregivers. This study is also expected to be a reference for educational institutions and a basis for developing further research with a wider range of variables.